Characteristics and phylogenetic analysis of the complete chloroplast genome of Paeonia japonica (Paeoniaceae) - Seo-Young Lim; Ji-Hun Jang; Hyun-Ju Lee; Seong-Sik Park; Sun-Ra Kim; Kyeong-Min Lee; Ji-Kyung Kim; Ho Park; Ho-Kyung Jung (Mitochondrial DNA. Part B. Resources, 2021)
Paeonia japonica, distributed throughout Asia, is a traditional medicinal herb in Korea, with many potential beneficial effects including pain-relieving, anti-inflammatory, and anti-cancer activities. Despite its high pharmacological value, the genetic information on Paeonia japonica remains limited. In this study, the chloroplast genome of P. japonica was sequenced using next-generation sequencing (NGS) technology and genome and phylogeny were analyzed using multiple tools. The chloroplast genome of P. japonica was 152,731 bp in length with an inverted repeat region of 26,656 bp, including a large single-copy region of 84,389 bp and a small single copy region of 17,030 bp. The P. japonica chloroplast genome included 113 genes comprising 80 protein-coding genes, 27 tRNA, and 5 rRNA genes. Phylogenetic analysis indicated that P. japonica and P. obovata share a close evolutionary relationship.